2019
DOI: 10.1007/s00423-019-01780-3
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation as a lifesaving procedure for posthepatectomy liver failure and iatrogenic liver injuries

Abstract: Background Iatrogenic injuries to vital structures of the liver and posthepatectomy liver failure are associated with high mortality. The current donor situation in Norway allows liver transplantation of patients beyond conventional criteria. Methods From 1984 to 2017, a total of 1510 liver transplantations were performed. In this retrospective study, we report the results of 13 patients undergoing liver transplantation due to iatrogenic injuries to the liver vasculature or posthepatectomy liver failure. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A recent publication by Thorsen et al could demonstrate the feasibility of liver transplantation to overcome PHLF if organ shortage isn't an issue. 42 Living donor liver transplantation could be an option when extended criteria are accepted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Thorsen et al could demonstrate the feasibility of liver transplantation to overcome PHLF if organ shortage isn't an issue. 42 Living donor liver transplantation could be an option when extended criteria are accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation is frequently stated to be the only definite treatment in patients with PHLF; however, the scientific evidence is low, and there are many obvious limitations. So far, three articles have described the experience with LTx in PHLF, two single-centre series 216 , 217 and a recent multicentre experience 218 . All concluded that it is safe and feasible to offer LTx to patients with PHLF with good long-term outcomes comparable to LTx for established indications; however, there are many unanswered questions such as the optimal time point for LTx and how to justify this indication in light of donor organ shortages.…”
Section: Treatmentmentioning
confidence: 99%
“…We have no obvious explanation for this. In the series reported by Otsuka et al, 14 five out of 7 patients were male and in the Oslo experience reported by Thorsen et al 15 out of 13 patients (five of which are included in the present study) were offered LTX for PHLF.…”
Section: Discussionmentioning
confidence: 61%
“…Despite this, LTX has been described in a limited number of scientific publications as a rescue option for PHLF patients. 14,15 However, several important questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%